Open-label, rapid initiation pilot study for extended-release buprenorphine subcutaneous injection. (2nd January 2023) - Hassman, Howard; Strafford, Stephanie; Shinde, Sunita N.; Heath, Amy; Boyett, Brent; Dobbins, Robert L.
ABSTRACT: Background: For patients with opioid use disorder, buprenorphine extended-release injection (BUP-XR) achieves sustained therapeutic plasma concentrations, controls craving and withdrawal symptoms, and improves patient outcomes. Given retention challenges during transmucosal buprenorphine (BUP-TM) induction, assessing methods to quickly achieve sustained buprenorphine concentrations is important. Objectives: This open-label, single-group, single-center pilot study (NCT03993392) evaluated safety and tolerability of initiating BUP-XR following a single BUP-TM 4 mg dose. Methods: Eligible participants abstained from short and long-acting opioids for 6 and 24 hours, respectively. If the Clinical Opiate Withdrawal Scale (COWS) was ≥8, BUP-TM 4 mg was administered. Participants not exhibiting hypersensitivity, precipitated opioid withdrawal (POW), or sedation symptoms within 1 hour received BUP-XR 300 mg (assessed as inpatients for 48 hours and outpatients to Day 29). Endpoints were COWS score increase ≥6, independent adjudication of POW, and opioid use. Results: Twenty-six participants (14 male) received BUP-TM, 24 received BUP-XR, and 20 completed the study. After injection, COWS scores decreased from pre-BUP-TM baseline of 14.6 ± 4.1 to 6.9 ± 4.1 at 6 hours and 4.2 ± 3.2 at 24 hours. Most participants (62.5%) experienced maximum COWS scores pre-BUP-XR; 2 experienced a COWS score increase ≥6, occurring at 1 and 2 hours post-BUP-XR. By adjudication, 2/24 participants experienced POW. Irritability, anxiety, nausea, and pain were the most frequent adverse events (AEs) with no serious AEs. Conclusions: Results support increased flexibility for initiating BUP-XR. Initiating BUP-XR 300 mg following a single BUP-TM 4 mg dose was well tolerated. Although some participants initially experienced withdrawal symptoms after injection, significant symptomatic improvement was observed in all participants within 24 hours.